Followership: boosting power and position in popular TV fiction - Mohd Muzhafar Idrus,; Ruzy Suliza Hashim,; Raihanah M. M., (Penerbit UKM, 2015)
Research by Andaya (1999) has shown that the “expansion of authority” in Southeast Asia is jostled through culture. In Malay archipelago, such authority and legitimacy are manifested in the regulation of “dress, language, and custom,” reinforcing powerful gains emanating from wide cultural control. Following this premise, we seek to provide insights that work in tandem with how culture evolves to signify one‟s power and position through conversational exchanges palpable in popular TV fiction. Specifically, in this paper, we argue that reasons related to culture including religion and communal beliefs are employed by the “dominant knower” to prevail in TV fiction‟s narrative exchanges. Based on Conversation Analysis (CA) of Julia and On Dhia, we show that “dominant knowers” triumph using Malay adat (customs), as a reasoning firstly to justify the behavior of everyday discourse (friendships, relationships, and parenthood) and secondly to explicate one‟s choices in instituting the roles of women and men in the Malay world. Through such analysis, it is also found that any arguments through logic are denied and eliminated. Given these findings, this study demonstrates whether followers do or do not possess agency and whether followership does or does not dwell on loyalty to friendship and kinship over the course of navigating their private and public lives. By focusing on the narrative exchanges, we also contend that although TV fiction evokes issues that are decidedly modern and liberal in response to forces of globalization, Malay adat is still powerful for boosting power and authority in everyday Malay discourse.